SNP rs3803264 polymorphisms in THSD1 and abnormally expressed mRNA are associated with hemorrhagic stroke - Chen, Changying; Gu, Xincheng; Liu, Fangyuan; Sun, Congyong; Mu, Jialin; Jin, Defu; Sui, Xuemei; Geng, Deqin; Li, Qingqing; Jiang, Yuzhang; Shen, Chong (Frontiers in Aging Neuroscience, 2023)
Background Thrombospondin Type 1 Domain Containing Protein 1 (THSD1) has been suggested to be a new regulator of endothelial barrier function in the angiogenesis process, preserving vascular integrity. We sought to characterize the association of THSD1 genetic variants and mRNA expression with the risk of hemorrhagic stroke (HS) with population-based evidence. Methods A case–control study was conducted with 843 HS cases and 1,400 healthy controls. A cohort study enrolled 4,080 participants free of stroke at baseline in 2009 and followed up to 2022. A synonymous variant, the main tag SNP rs3803264 of the THSD1 gene, was genotyped in all subjects, and peripheral leukocyte THSD1 mRNA expression was detected using RT-qPCR in 57 HS cases and 119 controls. Results In the case–control study, rs3803264 AG/GG variations are associated with a decreased risk of HS with odd ratio (OR) and 95% confidence interval (CI) of the dominant model of 0.788 (0.648–0.958), p = 0.017. In addition, rs3803264 and dyslipidemia had a multiplicative interaction [OR (95% CI) = 1.389 (1.032, 1.869), p = 0.030]. In the cohort study, a similar association strength of rs3803264 dominant model and the risk of HS was observed with the incidence rate ratio (IRR) of 0.734 and p-value of 0.383. Furthermore, the risk of HS showed a non-linear as THSD1 mRNA expression increased (p for non-linearity <0.001). For the subjects without hypertension, we observed THSD1 mRNA expression had a negative correlation with systolic blood pressure (SBP; ρ = −0.334, p = 0.022). Conclusion SNP rs3803264 polymorphisms in THSD1 are associated with the decreased risk of HS and interacted with dyslipidemia, and a non-linear association was observed between THSD1 mRNA expression and the risk of HS.